2021
DOI: 10.3389/fcell.2021.658720
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Inhibits Traumatic Brain Injury-Induced Neuron Apoptosis via EZH2-Downregulated KLF4/p38 Axis

Abstract: Traumatic brain injury (TBI) is characterized by physical damage to the brain tissues, ensuing transitory or permanent neurological dysfunction featured with neuronal loss and subsequent brain damage. Sevoflurane, a widely used halogenated anesthetic in clinical settings, has been reported to alleviate neuron apoptosis in TBI. Nevertheless, the underlying mechanism behind this alleviation remains unknown, and thus was the focus of the current study. First, Feeney models were established to induce TBI in rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In addition, anesthetics have been reported to trigger apoptosis (Shi et al, 2020;Wang et al, 2021). In agreement with this, we found that the number of apoptotic cells in the hippocampal tissues was significantly increased after SEV treatment and this was rescued by UAF1 downregulation.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, anesthetics have been reported to trigger apoptosis (Shi et al, 2020;Wang et al, 2021). In agreement with this, we found that the number of apoptotic cells in the hippocampal tissues was significantly increased after SEV treatment and this was rescued by UAF1 downregulation.…”
Section: Discussionsupporting
confidence: 89%
“…Our study should provide researchers with the necessary information to make study design and analytical decisions that result in more appropriate characterization of microglial morphology. We also note that the findings of our study might be applicable to other areas of neuroscience, because the morphology of neurons 15 , 32 34 and astrocytes 12 , 35 are commonly assessed using the same or similar immunohistochemistry techniques and metrics. Quantitative methods to describe microglial morphology should be selected based on several criteria including the research question, immunohistochemical experience of the researchers, and time required to isolate individual cells versus analyze full photomicrographs.…”
Section: Discussionmentioning
confidence: 91%
“…The primary aim was to investigate the potential benefits of sevoflurane intervention on PTSD and to determine its underlying mechanisms. In addition, previous studies have confirmed that sevoflurane has no significant effects on control samples (Wang et al 2021). Pretreatment with sevoflurane has been shown to effectively reduce the incidence of PTSD.…”
Section: Discussionmentioning
confidence: 92%